Notice of Retraction: Electrical Power Generation with Himalayan Mud Soil using Microbial Fuel Cell - Debajyoti Bose; Amarnath Bose (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2016)
Notice of Retraction-----------------------------------------------------------------------After careful review of the content of this paper by an expert committee, this paper has been found to be in violation of IAES' Publication Ethics and Publication Malpractice Statement (see: http://section.iaesonline.com/index.php/IJEEI/about/editorialPolicies)The Editors decided to retract the content of this paper. Reasonable effort should be made to remove all past references to this paper.-----------------------------------------------------------------------Topsoil microbial community primarily consists of bacteria species that can generate electricity if a microbial fuel cell is incorporated with it. Since such electron producing bacteria are abundant in nature, microbial fuel cells can be considered as clean source of electricity generation and a prospect for renewable energy growth.  Here, the authors have shown experiments with a real microbial fuel cell, investigating electrical power production from it using the Himalayan top soil of Dehradun in Uttarakhand, India. At the smallest level it can help remote rural areas to power lamps or other less energy intensive devices. Using a setup that includes anode, cathode, and related electrical fittings this work has utilized these bacteria over time and observe the power they produce; also the addition of nutrients to the soil which increases the rate of power production has also been experimented. The setup brings together the concept of energy, electronics and microbiology under one framework and is in line with issues relating to climate change, energy security and sustainability. An attempt has been made to explore the spectrum of scenarios and speculating the possibility of generating renewable power using the Himalayan top soil.